Photocatalytic direct intermolecular addition of 1, 3-dithianes. Issue 105 (13th October 2015) - Lee, Ming; Chen, Ying-Ho; Hung, Tzu-Hang; Chang, Wen; Yan, Wei-Cheng; Leow, Dasheng
Abstract : A direct intermolecular radical addition of 1, 3-dithianes to alkenes has been accomplished via visible-light mediated photocatalysis. Abstract : A direct intermolecular addition of 1, 3-dithianes to alkenes has been accomplished via visible-light mediated photocatalysis. This new process proceeds in moderate to excellent yields and eliminates the need for pre-functionalization of substrates. Electronic tuning of the 1, 3-dithiane plays a vital role in ensuring reactivity. Both aromatic and aliphatic aldehyde-derived 1, 3-dithianes are compatible. This radical umpolung strategy allows the synthesis of γ-keto-α-amino acid derivatives.